Route planning in the Palaeolithic? (poster) - Scott-Jackson, Julie; Scott-Jackson, William (Proceedings of the Seminar for Arabian Studies, 2013)
A systematic survey of the western fringes of the al-Ḥajar mountains to the south of Sharjah Emirate, by the PADMAC Unit during 2011, led to the discovery of ten Palaeolithic surface-sites/scatters in an area crossed at several points by the United Arab Emirates/Oman borders. In addition, the central area of the mountains adjacent to this region was surveyed but no stone tools of any description were found. The ten newly discovered Palaeolithic assemblages exhibit affinities to the fourteen Middle Palaeolithic assemblages we had previously found (2006—2008) in a similar context along the western fringes of the mountains, but further north in the Emirates of Sharjah and Raʾs al-Khaymah. This interim report examines the implications of these findings as they relate to the understanding of hominin dispersals and use of the landscape in this region, as all twenty-four Palaeolithic surfacesites/scatters occur on a clearly defined north–south line of foothills, with readily available resources of outcropping seams of knappable chert, wadi systems, small caves/rock-shelters, and long views to the west, over what are now alluvial fan gravel plains but areas of which may have been lakes at various times during the Palaeolithic period. The conspicuous distribution pattern of these Palaeolithic surface-site/scatters suggests, perhaps, hominin expansion along the western fringes of the al-Ḥajar mountains — a cognitive process of prediction, in which Palaeolithic people envisaged a suitable future location from a current preferred real location, in essence a ’Palaeolithic highway’.